No way to say "no": Stakeholder analysis for compulsory purchase for public infrastructure project in Australia. Issue 1 (19th February 2018) - Rao, Jyoti; Tiwari, Piyush; Hutchison, Norman
Abstract : Purpose: Property often forms the biggest component of household wealth and assets. Irrespective of landowners' willingness, the act of compulsory acquisition abruptly ceases the security that this ownership carries. This often induces dissatisfaction among affected landowners over the: loss of "property rights"; loss of commodity, or property; and loss of future opportunities associated with the property. Though there have been attempts in various land acquisition laws and a practice to compensate acquirees for their loss, the dissatisfaction of acquirees has persisted. The persisting resistance of landowners compels deeper insight into the process of compulsory purchase and the compensation mechanism to understand underlying causes for resistance. The purpose of this paper is to investigate the extent of involvement of these different stakeholders, at various stages in the compulsory purchase process, using stakeholder interaction analysis. Results obtained from this research will be helpful in identifying the gaps in the process of compulsory purchase of land for public projects in Australia. Design/methodology/approach: A survey of ten different stakeholder groups has been conducted to inquire the level of interaction of different stakeholders at various stages of compulsory purchase process. A comparative study was then performed to identify the gaps between the advocated process (suggested in the literature) and the process adopted by stakeholders. Findings: The results illustrate that: affected landowners seek involvement at the initial stage when the project plan is under preparation and compulsory purchase declaration are not finalised; objectors (from the public) seek opportunities to convey, to the public agency, their views even though the accountability of public agencies towards this stakeholder is nil; and strong interactions are established during negotiation over the compensation amount thus signifying the urge of acquirer and acquirees to avoid monetary losses and time delays. Originality/value: This research will be useful in identification of pain points in the compulsory purchase process for public projects. This shall help in evolution of fairer mechanism of land acquisition.